Physiological costs and age constraints of a sexual ornament: an experimental study in a wild bird. (8th February 2021) - McQueen, Alexandra; Delhey, Kaspar; Szecsenyi, Beatrice; Crino, Ondi L; Roast, Michael J; Peters, Anne
Abstract: Sexual ornaments are often considered honest signals of quality because potential costs or constraints prevent their display by low-quality individuals. Testing for potential physiological costs of ornaments is difficult, as this requires experimentally forcing individuals to produce and display elaborate ornaments. We use this approach to test whether a sexually selected trait is physiologically costly to male superb fairy-wrens ( Malurus cyaneus ). Male fairy-wrens molt from brown to blue breeding plumage at different times of the year, and females strongly prefer the few males that are blue early, during winter. We used short-acting testosterone implants to stimulate males to produce "early-blue" plumage and assessed costs during and after molt using a panel of physiological indices. Testosterone-implanted, T-males molted in winter and produced blue plumage 6 weeks before control-implanted, C-males. T-males molted while in lower body condition, tended to have lower fat reserves, and were more likely to be parasitized by lice. However, we detected no negative effects on immune function, blood parasites, exposure to stressors, or survival. Juvenile males never naturally display early-blue plumage, but we found no evidence for increased costs paid by juvenile T-males. Instead, juvenile T-males molted later than adult T-males, suggesting that age presents an absolute constraint on ornament exaggeration that cannot be fully overcome by testosterone treatment. Together, these small costs and large, age-related constraints may enforce signal honesty, and explain female preference for early-blue males. Abstract : Sexually attractive, ornamental traits are expected to honestly signal mate quality because costs prevent low-quality individuals from investing in ornaments. Despite this, we found little evidence for costs due to experimentally forced ornament production in wild, male superb fairy-wrens. We show that young male fairy-wrens are less capable of producing ornaments compared to adults. Our findings suggest small, physiological costs and substantial, age-related constraints could enforce signal honesty, and explain female preference for ornamented males.